When Do Ethical Leaders Become Less Effective? The Moderating Role of Perceived Leader Ethical Conviction on Employee Discretionary Reactions to Ethical Leadership - Babalola, Mayowa T. (Journal of business ethics, 2019)
Drawing from the group engagement model and the moral conviction literature, we propose that perceived leader ethical conviction moderates the relationship between ethical leadership and employee OCB as well as deviance. In a field study of employees from various industries and a scenario-based experiment, we revealed that both the positive relation between ethical leadership and employee OCB and the negative relation between ethical leadership and employee deviance are more pronounced when leaders are perceived to have weak rather than strong ethical convictions. Further, we argued and showed that employees’ feelings of personal control and perceived voice opportunity mediated the interactive effect of ethical leadership and perceived leader ethical conviction on OCB and deviance. Implications of these findings for theory and practice are discussed.